Field of the Administrative Geography of the Sasanian Empire on the Auspicious Occasion of the Publication of La Géographie Administrative de l’Émpire Sassanide. Les Témoignages Épigraphiques en Moyen-Perse - Hossein Habibi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2022)
The political and administrative structures of the Sasanian Empire have been the focus of numerous research. For the rather recent developments of the subject, though, Rika Gyselen’s studies have been crucial. Thirty years after her trailblazing 1989’s book in the field, the publication of La géographie administrative de l’empire sassanide. Les témoignages épigraphiques en moyen-perse have brought about these developments fulfilled and provided us with yet another monumental work of research on the dynamics of the administrative geography of the state. Therefore, the main focuses of this essay are concerned with the review of the latter book and the progress it achieved in the field, along with the academic background of the author. To that end, the content of each chapter is meticulously presented and its potentialities for authorities is noted. Then, some points that could have improved the work and helped it to meet further expectations of an even more comprehensive repertoire, together with suggestions for future research, are succinctly provided. The book delivers a factual account while founding the research design on the examination of Middle-Persian epigraphic primary sources. Therefore, a catalogue raisonné presents a state-of-the-art corpus of Sasanian scholarship according to a diachronic-comparative approach.